Language Preservation and Cultural Continuity: The Tengger Javanese Dialect and the Role of Tradition in Its Sustenance - Fathi, Revina Lutfi Al; Salamah; Satwika, Pratista Widya; Salma, Wakhidatus; Sutopo, Firaas Zhaafirah Sairtynnahd; Sukmawan, Sony (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2026)
Local languages continue to experience the threat of diglossia leakage. This study analyzes the vitality of the Tengger Javanese Dialect (BJDT), the role of women in the preservation of BJDT through traditional practices, and opportunities for the preservation of BJDT in other public spaces. A descriptive qualitative research design with a field study approach was implemented in Tosari Village, using interview techniques, observation, and literature review for data collection. Upon data collection, analysis was conducted based on the UNESCO language vitality indicators and cultural theme analysis. The research findings indicate that BJDT falls into the vulnerable category, as determined by the nine language vitality indicators. The evaluation of the issue leans toward the transmission of the language to younger generations, highlighting the need for the role of women, especially mothers, as the primary educators for children. A folkloric approach was employed to examine traditions passed down within the community, such as kumpul perapen in the private domain and bethek-sinoman in the public or local community domain. The opportunity for revitalizing BJDT in other public spaces could be realized through the preparation of a policy brief for local government addressing language policy issues that involve the local community. This research demonstrates how women’s traditional practices are central to sustaining BJDT, offering a framework that integrates community involvement, local government support, cultural documentation, and policy development to strengthen preservation efforts and expand scholarly understanding of this vulnerable tradition today.